2021
DOI: 10.47626/1679-4435-2021-812
|View full text |Cite
|
Sign up to set email alerts
|

Association between musculoskeletal pain and telework in the context of the COVID‑19 pandemic: an integrative review

Abstract: Direitos para esta edição cedidos à Atena Editora pelos autores. Todo o conteúdo deste livro está licenciado sob uma Licença de Atribuição Creative Commons. Atribuição-Não-Comercial-NãoDerivativos 4.0 Internacional (CC BY-NC-ND 4.0). O conteúdo dos artigos e seus dados em sua forma, correção e confiabilidade são de responsabilidade exclusiva dos autores, inclusive não representam necessariamente a posição oficial da Atena Editora. Permitido o download da obra e o compartilhamento desde que sejam atribuídos cré… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 33 publications
(37 reference statements)
3
8
0
Order By: Relevance
“…A previous integrative review by dos Santos et al found that musculoskeletal pain increased during the lockdowns, especially in the lower back and neck regions, which could be explained by an increased sedentary lifestyle, poor posture, and increased physical load due to household chores [ 14 ]. However, compared to this review, more studies were found due to the updated search, and the risk of bias was assessed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous integrative review by dos Santos et al found that musculoskeletal pain increased during the lockdowns, especially in the lower back and neck regions, which could be explained by an increased sedentary lifestyle, poor posture, and increased physical load due to household chores [ 14 ]. However, compared to this review, more studies were found due to the updated search, and the risk of bias was assessed.…”
Section: Discussionmentioning
confidence: 99%
“…Medically codified diseases are included in this definition, like carpal tunnel syndrome or rotator cuff disease, but unspecific conditions like low back pain or neck pain are also included. Although there were some studies on the impact of teleworking on mental health before the COVID-19 pandemic [ 12 ], few of them focused on MSD [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the prevalence of neck pain was significantly related to age, sex, health status, job satisfaction, and length of employment. In addition, an increased sedentary lifestyle and incorrect posture appear to promote the onset of musculoskeletal disorders [ 22 ]. The main prevention strategies for avoiding these consequences are: reducing smartphone usage time, maintaining correct posture, performing exercise regularly, and teaching healthy habits.…”
Section: Introductionmentioning
confidence: 99%
“…Since the coronavirus disease 2019 (COVID‐19) pandemic, teleworking, also known as remote working, has become a new norm for many workers. While there are also findings to the contrary (Argus & Pääsuke, 2021; Rodríguez‐Nogueira et al, 2021), the incidence of musculoskeletal pain has been described as widespread or has increased among these workers during this time (Chirico et al, 2021; Gerding et al, 2021; McAllister et al, 2022), particularly in the back, neck (dos Santos et al, 2021), and shoulders (Gerding et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Teleworkers have also been found to spend more time on the computer than when working in an office and changing posture less frequently (McAllister et al, 2022), but contrary findings have also been presented (Widar et al, 2021). Teleworkers have been described as feeling less comfortable working from home than in the office (Argus & Pääsuke, 2021), and aspects such as poor posture among teleworkers (Aksüt et al, 2022; dos Santos et al, 2021), poorly chosen work equipment (Gerding et al, 2021), poorly adjusted equipment (MacLean et al, 2022), and a sedentary lifestyle have been associated with the development of musculoskeletal pain in teleworkers (dos Santos et al, 2021). Other studies have failed to establish a link between poor ergonomic arrangements in teleworkers and the development of musculoskeletal pain (El Kadri Filho & Roberto de Lucca, 2022; McAllister et al, 2022).…”
Section: Introductionmentioning
confidence: 99%